Experimental Design for the Observation of Saliva Droplets Using a High-Speed Camera - Rachmad Almi Putra; Hamdani Umar; Samsul Rizal; Maimun Syukri; Salamul Fajar (Postgraduate, University of Mataram, 2023)
Disease transmission is often caused by viruses or bacteria contained in salivary droplets. Salivary droplets are produced from breathing, coughing, and sneezing activities. The extent of droplet dispersal can determine the safe distance between individuals when interacting, many studies have taken a simulation and modeling approach, arguing that the risk of exposure to pathogens. In this study, we attempted to set up an instrument to experimentally observe the flow of saliva droplets emitted during sneezing using a High-Speed Camera (HSC) model Phantom T-1340 without using a light sheet. Additionally, this study did not use lasers for the comfort and safety of individuals during recording of sneezing phenomena. The observation results explain that the sneezing phenomenon occurs within a time frame of 300 ms. The number of droplets observed was 246 with an observation probability of only 66%. The saliva fluid emitted is considered as large particles (bulk droplets) that undergo refraction due to two main factors, namely external and internal factors. External factors are influenced by environmental air flow rate, humidity, and temperature. Internal factors refer to the contents present in saliva such as water, protein, enzymes, and mucus or mucin.